Soil quality in the current EU policies - Wieliczko, B. (НУБіП України, 2023)
Since the announcement of the European Green Deal, the EU policies have been increasing their environmental ambitions and introducing policy measures and standards that are supposed to support the EU in the efforts to reach zero-net emissions, protection of biodiversity and climate change mitigation and adaptation. Soil health issues are among these efforts. The paper briefly presents the current policies (already in place and in the discussion process) focusing on the soil quality. The study shows that there is no common agreement on following the path determined by the European Commission, thus achieving the environmental goals can be hindered.
Keywords: soil quality; якість ґрунтів; Bodenqualität